Effect of Oxidized Low Density Lipoprotein on Thrombomodulin Expression by THP-1 Cells - Oida, Koji; Tohda, Gen; Ishii, Hidemi; Horie, Shuichi; Kohno, Mitsuyuki; Okada, Eiko; Suzuki, Jinya; Nakai, Jsuguhiko; Miyamori, Isamu (Thrombosis and Haemostasis, 1997)
We have investigated the effects of oxidized low density lipoproteins (oxidized LDL) on the expression of TM by THP-1 monocytic cells. TM antigen levels and its cofactor activity for thrombin-dependent protein C activation were increased by oxidized LDL and accompanied by an increase in TM mRNA levels. Incubation of THP-1 cells with 300 μg/ml oxidized LDL for 24 h resulted in an 80% increase of cellular TM antigen levels. Native LDL and acetylated LDL did not affect the TM expression by these cells. The resultant aqueous phase after extraction of oxidized LDL by chloroform/methanol increased the TM antigen levels as well as oxidized LDL. Phorbol 12-myristate 13-acetate (PMA) also increased the TM antigen level 2.1 times the control and was accompanied by the adhesion of cells to plastic dishes and increasing macrophage cell surface antigen CD 14 levels. In contrast, oxidized LDL did not induce differentiation to the macrophage. The present results indicate that oxidized LDL increases cellular TM antigen without cellular differentiation and that up-regulation of TM by oxidized LDL in monocytes may have some implication in atherosclerosis.